Emerging economic systems in Central and Eastern Europe – a qualitative and quantitative assessment - Clemens Buchen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2010)
In a first step, more generally, the concept of institutional arbitrage within the comparative capitalism literature is put to a test: as a result of comparative institutional advantages due to different investment incentives provided by types of institutions, companies relocate activities to countries, where the institutional set-up best supports a given activity. We test this proposition using German outward FDI figures on a sectoral level. We find evidence of institutional arbitrage using different ways to operationalize system differences between countries. Evidence crucially depend on the size of the receiving sector. FDI in a sector with comparative institutional advantage increases with sector size, while for a sector without a comparative institutional advantage the size of the sector does not matter. In a next step, the concept of the Varieties of Capitalism approach is applied to two Eastern European countries, Estonia and Slovenia, thereby assessing the general applicability of the postulated rcomplementarities-framework. In five spheres of the economy the institutional configuration is analysed: industrial relations, corporate governance, inter-firm relations, social security and vocational training. Slovenia seems to exhibit western style features of a coordinated market economy in all areas under study. Estonia is organised very liberally, as we would expect from a liberal market economy. However, in the sphere of corporate governance in both cases we identify deviations from institutional complementarities of advanced capitalist systems. Lastly, in a more general setting involving a larger sample of Central and Eastern European countries, a number of econometric approaches is used to assess the explanatory power of competing theories of institutional emergence and change. Political economy, legal origin and cultural notions of institutional determinants are tested.
urn:nbn:de:101:1-201008171268; Additional information: Article 2 is published as: Buchen, Clemens, 2007. Estonia and Slovenia as Antipodes. In: Lane, David, Myant, Martin (eds), Varieties of Capitalism in Post-Communist Countries. Palgrave Macmillan, Houndmills, New York, 6565. 65-89.
Keywords: P10; P30; P16; P52; F21; F23; 330; New Institutional Economics; Central and Eastern Europe; Transition; Varieties of Capitalism; Foreign Direct Investment; Neue Institutionenökonomik; Osteuropa; Transformationsstaaten; Varieties of Capitalism